Comparing the Efficacy and Patient Satisfaction in Treatment of Facial Static Wrinkles Using CO2 Fraxel Laser Alone or with Radiofrequency - Mohammad Ali Nilforoushzadeh; Amir Hossein Siadat; Farnaz Nasr-Esfahani; Elaheh Haft-Baradaran (مجله دانشکده پزشکی اصفهان, 2014)
Background: Lasers and light-based treatments are currently the standard and useful methods for treating various stages of aging. Several studies have shown that the most successful results in treating wrinkles are achieved via combination of different treatment protocols. In this study, we compared the efficacy and patient satisfaction in treatment of facial static wrinkles using CO2 fraxel laser alone or with radiofrequency.